RUMAH INOVASI DAUR ULANG (RINDU) SOLUSI KREATIF PENGOLAHAN LIMBAH UNTUK MASA DEPAN BERKELANJUTAN - Rahmawati, Lily; Nur Fadhilah, Destri; Maulana, Sukma; Safira, Dira; Rayvani, Rofiqoh (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The Rumah Inovasi Daur Ulang (RINDU) is an initiative offering creative and sustainable solutions for waste management, particularly plastic waste, which has become a major environmental issue in Indonesia. This program was initiated by the Gajahlah Kebersihan community and focuses on empowering the community in Pulau Pasaran, Lampung. Through a collaborative approach, RINDU integrates environmental education, eco-social research, eco-edutourism, and eco-entrepreneurship to create a holistic waste management ecosystem. One of RINDU’s flagship innovations is the eco-roster, a construction material made from recycled plastic waste that is not only environmentally friendly but also holds significant economic value. RINDU successfully raises public awareness through waste sorting training and the production of recycled goods while creating job opportunities for the local community. Additionally, the program leverages technology and cross-sector partnerships to ensure the sustainability of its projects. In its journey, RINDU faces challenges in educating the public and requires broader support, including from the government and private sectors. RINDU’s success serves as concrete evidence that community-based social innovation can make a substantial impact in creating cleaner environments, competitive economies, and empowered communities.